The Impact of Span Width and Outrigger Shape on Fishing Boats at Palabuhanratu Fishing Port, Indonesia - Fikri Rizky Malik; Yopi Novita; Budhi Hascaryo Iskandar; Gondo Puspito; Sri Suryo Sukoraharjo (International Journal of Marine Engineering Innovation and Research, 2024)
Outrigger boats are prevalent in Indonesian waters. In Indonesia, the majority of Outrigger boats have a gross tonnage of less than 7 GT, resulting in their classification as "boats." After being hit by waves, the outrigger serves as a balancing mechanism on the boat, ensuring that it does not capsize and that it continues to keep its stability. In spite of the fact that they have a number of benefits, outrigger boats also have a number of drawbacks. One of these drawbacks is that they need a mooring space that is sufficiently large to anchor the boat at the beach or pier. This research was carried out through the use of experimental methodologies. The stability value is a reference to the design parameters established by IMO A.749 (18), which are applicable to all boats. Type 2 boats have a maximum GZ value that is greater than that of type 1 boats. According to the findings of the study, the utilization of the Palabuhanratu pool was increased by 33% on model B boats and by 52% on boat C when the outrigger boom was pulled while the boat was in the port pool. This was in comparison to the original value when the boat was anchored without pulling the outrigger boom.